Bizarro, Sara. “A Hertzian Interpretation of Wittgenstein’s Tractatus” - Mario Pardo (Ideas y Valores)
Bizarro, Sara. "A Hertzian Interpretation of Wittgenstein's Tractatus", Eidos 13 (2010): 150-165.